Adding eptinezumab to brief patient education to treat chronic migraine and medication-overuse headache: Protocol for RESOLUTION—A phase 4, multinational, randomized, double-blind, placebo-controlled study - Jensen, Rigmor H.; Schytz, Henrik Winther; Tassorelli, Cristina; Terwindt, Gisela M.; Carlsen, Louise N.; Mittoux, Aurélia; Østerberg, Ole; Lipton, Richard B.; Tepper, Stewart J.; Blumenfeld, Andrew; Lundqvist, Christofer (Frontiers in Neurology, 2023)
Introduction Migraine is a highly prevalent and disabling neurological disease. Excessive use of acute medications can lead to medication-overuse headache (MOH), occurring when a patient experiences an increasing number of headache and migraine days, despite taking greater amounts of acute medication. To treat MOH, a preventive migraine treatment and/or withdrawal of the overused medication(s) are advised. Brief Educational Intervention (BEI) has been shown to be an effective tool with promising results for MOH. Here, we report the design of a clinical trial that aims to evaluate the efficacy of eptinezumab, an anti-calcitonin gene-related peptide preventive migraine treatment, as an add-on to BEI for treatment of MOH in those with chronic migraine. Methods and analysis RESOLUTION will be a phase 4, multi-national, randomized, double-blind, placebo-controlled study. This study will enroll approximately 570 participants with dual diagnoses of chronic migraine and MOH. Eligible patients will be randomly allocated to one of two treatment groups, BEI and eptinezumab (100 mg; n = 285) or BEI and placebo (n = 285), in a 1:1 ratio. The primary endpoint is the change from baseline in monthly migraine days over weeks 1–4. Secondary and exploratory endpoints will assess monthly migraine days over weeks 1–12, MOH remission, transition from chronic to episodic migraine, health-related quality of life, work productivity, and the safety and tolerability of eptinezumab in this patient population. Ethics and dissemination This study will be conducted in accordance with good clinical practice. All patients will be fully informed about the study, including the risks and benefits of participation, and all participants will provide informed consent for participation in the trial and dissemination of results.